Análise do uso da Ultrassonografia Pulmonar focalizada em bezerros - Gabriela Anteveli (2024)
Bovine respiratory disease (BRD) poses significant challenges on beef and dairy farms, impacting mortality rates, animal welfare, and production efficiency. Although pulmonary ultrasonography is highly sensitive and specific for monitoring lung lesions and diagnosing BRD, its practical application could be optimized by focusing on the most commonly affected lung lobes. This study firstly evaluated the efficacy of focused lung ultrasonography for diagnosing BRD in calves, examining individual lung lobes and their associations versus the extensive lung scanning under various disease prevalence scenarios. Then, the relationship between individual and combined clinical respiratory signs vs lung consolidation was analyzed. 193 Holstein calves from a longitudinal study, evaluated over different weeks, were used in conjunction with 112 Angus from a cross-sectional study, totaling 1153 evaluations from 1 to 6 months of age using complete bilateral thoracic ultrasonography, the agreement and sensitivity of specific lung lobes combination vs the total lung ultrasound findings. The Classification and Regression Tree (CART) algorithm was used to suggest an optimal examination sequence, and logistic regression was applied to associate specific clinical signs with the presence of lung consolidation adjusting for breed and calf age. Findings reveal that the most sensitive areas are the caudal (K: 0.433; Se: 40,3%) and cranial (K: 0.867; Se: 84,7%) portions of the right cranial lobe, the caudal portion (K: 0.235; Se: 20,6%)of the left cranial lobe, and the middle lobe (K: 0.25; Se: 22%).. The optimal lobe combinations for focused lung ultrasonography were identified as the right cranial lobe paired with either the left cranial lobe or the middle lobe. Focused techniques achieved sensitivity over 94% and maintained good agreement. Using these focused techniques were relatively robust to various true lung consolidation. CART analysis recommended initiating examinations with the right cranial lobe, proceeding to the left cranial lobe, and concluding with the middle lobe. While spontaneous cough was linked to pneumonia presence, reliance on a single clinical sign is not advised due to moderate sensitivity (81,47%) and low specificity (74,83%); it should merely prompt further ultrasound assessment. In conclusion, focused lung ultrasonography, especially utilizing the right cranial lobe in conjunction with the left cranial lobe or the middle lobe, emerged as effective strategies for focused pulmonary ultrasonography, preserving the accuracy of the results.